The Correlation between Self-Concept and Optimism among Psychology Faculty of College Students Who Compiled on Thesis at University of Medan Area - Wahyuni, Nini Sri; Istiana, Istiana; Asri, Jannah Safira (Budapest International Research and Critics University, 2021)
This study aims to determine the relationship between self-concept and optimism in students of the Faculty of Psychology who prepare thesis at the University of Medan Area. The population in this study were students of the 2016 who were in the process of writing a thesis and had conducted a seminar proposal totaling 270 people. The sample of this research is 68 people. The sampling technique used in this research is incidental sampling. The data collection tool used was a self-concept scale based on Berk's theory (in Dariyo, 2007) consisting of 48 items (Î± = 0.713) and a scale of optimism based on Seligman's theory (2008) consisting of 48 items (Î± = 0.763 ). Data analysis using Pearson Product Moment correlation technique with correlation coefficient value ( ) = 0,545 and p = 0.000 (p < 0.05), which means that there is a significant positive relationship between self-concept and optimism in preparing theses for students of the Faculty of Psychology, Medan Area University. which indicates that the hypothesis in this study is accepted. The higher the self-concept of the subject, the higher the optimism of the students of the Faculty of Psychology, Medan Area University in preparing their thesis. The self-concept has a role on optimism in completing the thesis by 29.7%.